Efecto protector del factor de crecimiento de hepatocitos (HGF) en un modelo murino de colestasis - Salas Silva, Elsy Soraya (Universidad Autónoma Metropolitana, 2016)
Cholestasis is a condition associated with a full or partial reduction in the bile flow that reaches the duodenum, caused either by a mechanical blockage impeding the normal flow of bile through the intra an d extrahepatic bile ducts (obstructive cholestasis) or due to alterations on the hepatocellular or ductular mechanisms of bile formation (functional cholestasis). Since it is an often a serious health condition with limited therapeutic options both in number and efficacy, it is necessary to carry out studies with potentially therapeutic molecules that could prevent or co unteract the damage generated by this pathology. Such is the case of hepatocyte growth factor (HGF), a growth factor with powerful antioxid ant, proliferative, anti - apoptotic and motility - stimulating effects, among others. To perform these effects, this growth factor requires activation of many transcription factors, including Nrf2, which regulates, through its target genes, the redox balance within the cell. Cholestasis is a condition associated with a full or partial reduction in the bile flow that reaches the duodenum, caused either by a mechanical blockage impeding the normal flow of bile through the intra - and extrahepatic bile ducts (obstructive cholestasis) or due to alterations on the hepatocellular or ductular mechanisms of bile formation (functional cholestasis). Since it is an often a serious health condition with limited therapeutic options both in number and efficacy, it is necessary to carry out studies with potentially therapeutic molecules that could prevent or co unteract the damage generated by this pathology. Such is the case of hepatocyte growth factor (HGF), a growth factor with powerful antioxid ant, proliferative, anti - apoptotic and motility - stimulating effects, among others. To perform these effects, this growth factor requires activation of many transcription factors, including Nrf2, which regulates, through its target genes, the redox balance within the cell. In this study, we evaluated the ant i - cholestasic capacity of HGF to counteract the damage caused by ANIT (a well-known model of cholestasis), and also the activation of Nrf2 as a putative key factor in the anti - cholesta t ic HGF effect. We o bserved that HGF has clear anti - cholestasic effects, because serum biochemical markers of liver integrity were improved, and liver histological ANIT injury decreased. This could be explained because this growth factor produced an enhancement in the express ion of basolateral and canalicular efflux transporters and of antioxidant enzymes induced by Nrf2. O ur results allow us to propose HGF as a highly efficient anti - cholestasic agent for the first time.; La colestasis es un síndrome asociado a una reducción total o parcial del flujo biliar que llega al duodeno, producto de un bloqueo mecánico que impide su paso a través de las vías biliares intra o extrahepáticas (colestasis obstructiva) o a alteraciones hepatobiliares de los mecanismos hepatocelulares o ductulates de formación de bilis (colestasis funcional). Debido a su frecuente gravedad y las limitadas alternativas terapéuticas con que se cuenta, tanto en número como en eficacia, es necesario realizar estudios con moléculas potencialmente terapéuticas que permitan evitar o contrarrestar el daño ocasionado por esta patología. Tal es el caso del factor de crecimiento hepatocitos (HGF), el cual es un factor de crecimiento con potentes efectos antioxidantes, proliferativos, antiapoptóticos, y de motilidad, por mencionar algunos. Esto lo hace activando diversos factores de transcripción, como Nrf2, el cual regula el estado redox de la célula a través de sus genes blanco. En el presente estudio, se evaluó la capacidad anticolestásica de HGF ante el daño por ANIT (un conocido modelo de colestasis), y se indagó la activación de Nrf2 como un posible factor clave en los efectos anticolestásicos de HGF. Se observó que HGF tiene claros efectos anticolestásicos, ya que restableció los niveles séricos de las pruebas bioquímicas de integridad hepática e indujo una mejora en las lesiones histológicas hepáticas ocasionad as por ANIT. Esto s e de be a que el HGF produjo un aumento en la expresión de transportadores basolaterales y canaliculares de exportación y enzimas antioxidantes que son activadas por Nrf2. Nuestros resultados permiten proponer por primera vez a HGF como un agente anticolestásico altamente eficiente.